2003
DOI: 10.1152/jn.00500.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connections Between Auditory Cortex on Heschl's Gyrus and on the Lateral Superior Temporal Gyrus in Humans

Abstract: Functional connections between auditory fields on Heschl's gyrus (HG) and the acoustically responsive posterior lateral superior temporal gyrus (field PLST) were studied using electrical stimulation and recording methods in patients undergoing diagnosis and treatment of intractable epilepsy. Averaged auditory (click-train) evoked potentials were recorded from multicontact subdural recording arrays chronically implanted over the lateral surface of the superior temporal gyrus (STG) and from modified depth electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
75
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 58 publications
20
75
0
Order By: Relevance
“…Howard and colleagues (Howard et al, 2000;Brugge et al, 2003) observed that stimulation of the medial half of Heschl's gyrus yielded the highest activity recorded in ipsilateral posterior STG, demonstrating that medial portions of Heschl's gyrus and posterior STG are components of the same neuronal circuitry. Based on their observations and the intracranial recordings of Liegeois-Chauvel et al (1991, it was argued that the planum temporale was a likely intermediary point between medial Heschl's gyrus and posterior STG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howard and colleagues (Howard et al, 2000;Brugge et al, 2003) observed that stimulation of the medial half of Heschl's gyrus yielded the highest activity recorded in ipsilateral posterior STG, demonstrating that medial portions of Heschl's gyrus and posterior STG are components of the same neuronal circuitry. Based on their observations and the intracranial recordings of Liegeois-Chauvel et al (1991, it was argued that the planum temporale was a likely intermediary point between medial Heschl's gyrus and posterior STG.…”
Section: Discussionmentioning
confidence: 99%
“…Activation in PAC (approximately the posterior half of Heschl's gyrus (HG), ϳ400 voxels in the T 1 -weighted anatomical dataset) was defined as the initial reference VOIs and used during GCM analysis to identify effective connectivity in the auditory cortex. To define the PAC on Hes-chl's gyrus, we used a combination of past anatomical work by Hackett et al (2001), Morosan et al (2001), and Rademacher et al (2001), in conjunction with results from intracranial recording studies in humans by Howard et al (2000) and Brugge et al (2003). Furthermore, the transverse temporal sulcus was used to define the border between Heschl's gyrus and planum temporale (PT), whereas the first temporal sulcus was used to define the border between Heschl's gyrus and planum polare.…”
Section: Methodsmentioning
confidence: 99%
“…Reciprocal connections between belt and parabelt regions and core auditory cortex, as described in the monkey (Hackett et al, 1998(Hackett et al, , 2014Kaas and Hackett, 1999;Hackett, 2008Hackett, , 2011, if present in humans could potentially transmit topdown motor commands (efference copies) to core auditory cortex, providing an interface for sensory-motor interactions to monitor and correct vocal output using the auditory feedback. Human ECoG studies have shown robust functional connectivity between core auditory cortex and surrounding auditory fields (Brugge et al, 2003) as well as between auditory cortex on HG and ventral prefrontal cortex (Garell et al, 2013;Kingyon et al, 2015). Thus, although the data from the present study do not delineate the anatomical pathways that are engaged to modulating auditory feedback processing during vocal production, they are consistent with available evidence for functional interactions between sensory-motor cortical networks considered to be involved in speech motor control.…”
Section: Neural Responses To Pitch-shifted Auditory Feedback In Hgmentioning
confidence: 99%
“…This is in line with the present finding of enhanced activity in primary auditory cortex for congruent audiovisual stimulation. Given the connections between STC and primary auditory cortex (Brugge, Volkov, Garell, Reale, & Howard, 2003;Howard et al, 2000), it is conceivable that STC communicates integrated information to earlier auditory cortices and that this process maybe occurs to a lesser degree if auditory and visual information streams do not match.…”
Section: Candidate Mechanisms Of Multisensory Integrationmentioning
confidence: 99%